Abelmoschus odishae (Malvoideae: Malvaceae): a new wild okra from tropical Eastern India - Misra, R. C. (Phytotaxa, 2023)
Abelmoschus odishae (Malvoideae: Malvaceae), a new species, from a moist deciduous forest in Keonjhar district of Odisha in Eastern India, is described and illustrated. It shares morphological similarities with A. palianus, however, differs in characters exhibiting perennial large shrub; densely hispid prickly stem with long retrorse hairs; spinescent pedicel; 8 (7–9) segmented, lanceolate epicalyx; widely campanulate corolla; ovoid to oblong, bristly capsules; sub-reniform seeds with stout porrect trichomes. A field identification key for Indian Abelmoschus is also provided for ease of identification.